Application of Scrum Method in the Design of Water Bill Payment Report Information System at BUMdes Mbinalun - Putri, Berlianda Oktariani Jelita; Al-Khowarizmi (Yayasan Asmin Intelektual Berkah, 2024)
An information system comprises components that process data, transforming it into meaningful information and assisting in the achievement of organizational objectives. The report information system on the design and development of this system is web-based, using the scrum methodology, which has flexible properties to develop a data processing application. However, the information system for processing water bill report data carried out at BUMDes Mbinalun still uses Microsoft Excel, so that the resulting data contains many errors in its management. Thus, the Scrum method makes work or data processing neater because the development process uses sprints, which are development activities to achieve small goals (which are broken down from the main goal) that usually take 2-4 weeks, which is called TimeBox. The final result of this work is a web-based water bill payment report system to make it easier to record water bill reports such as customer data, basic tariff data, and usage data. Apart from that, the design of the water bill payment report information system also provides information in the form of reports that can be printed directly, and customers can view bill data on the web.